2015
DOI: 10.1002/adfm.201503247
|View full text |Cite
|
Sign up to set email alerts
|

Kitchen Chemistry 101: Multigram Production of High Quality Biographene in a Blender with Edible Proteins

Abstract: A facile method for producing unoxidized, pristine graphene under biologically benign conditions is essential for widespread biomedical applications of graphene. Rate of exfoliation, scalability, high quality, controlled functionalization, size and large fl ake size are highly desired. Rapid production of biofunctionalized, micrometer size, and defect free, few layer graphene (FLG) is reported here. Further, we have systematically examined Kitchen Chemistry 101: Multigram Production of High Quality Biographene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(140 citation statements)
references
References 42 publications
6
134
0
Order By: Relevance
“…The efficiencies are compared with our previous study which used bovine serum albumin (BSA, 3.0 mg/mL, 4.0 mg mL -1 h -1 ) 8 and 10% serum contains similar levels of total protein in serum. Thus, the comparable levels of graphene efficiencies suggest that serum proteins may be the primary active species responsible for the observed exfoliation efficiencies in these sera.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiencies are compared with our previous study which used bovine serum albumin (BSA, 3.0 mg/mL, 4.0 mg mL -1 h -1 ) 8 and 10% serum contains similar levels of total protein in serum. Thus, the comparable levels of graphene efficiencies suggest that serum proteins may be the primary active species responsible for the observed exfoliation efficiencies in these sera.…”
Section: Resultsmentioning
confidence: 99%
“…Direct exfoliation of graphite to graphene in water is achieved by using small organic molecules, 12 amphiphilic stabilizers such as surfactants, 13 proteins, 8,14,15 and carbohydrates. 16 The reagent used for this process (exfoliating agent) should stabilize graphene in water, but it should not be toxic to most biological systems, if the preparations are to be used for biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have pursued this by exfoliation of graphite in aqueous media with, for example, pyrene derivatives, [10][11][12] anionic surfactants, 13,14 polymers, 15,16 or proteins. [15][16][17][18] Therefore, whereas GO powders can be directly dispersed in the cell culture medium (CCM) or transferred through dilution from water, 8 pristine (chemically non-modified) GR in aqueous suspension is mostly handled with its accompanying dispersant, 15,17 or (hardly ever reported) GR powders directly dispersed in CCM. 19 However, these latter authors found adsorptive artifacts due to GR large surface area, which cause non-covalent interactions with the CCM components.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, shear mixer was introduced to exfoliate the graphite into individual graphene nanosheets [3,4,[38][39][40]. Because the oxygen-containing groups binding on carbon atoms will increase the interlayer spacing of graphite oxide, and make the layered graphite oxide easier to cleave [10,41].…”
Section: Introductionmentioning
confidence: 99%